Astrocytes underlie a faster-onset antidepressant effect of hypidone hydrochloride (YL-0919) - Li, Jin-Feng; Hu, Wen-Yu; Chang, Hai-Xia; Bao, Jin-Hao; Kong, Xiang-Xi; Ma, Hui; Li, Yun-Feng (Frontiers in Pharmacology, 2023)
Major Depression Disorder (MDD) is a common and potentially life-threatening mental illness, which currently lack of confirm pathogenesis and effective therapeutic measure. Pathological changes of astrocytes play a pivotal role in MDD, and hypidone hydrochloride (YL-0919), an independently developed antidepressant, showed rapid action with low side effects, however, its underlying astrocyte-specific mechanisms remain unclear. In our study, mice were exposed to chronic restraint stress (CRS) for 14 days or concomitantly administrated with YL-0919/fluoxetine; behavioral tests were applied to evaluate depression model; immunofluorescence and immunohistochemistry staining were used to explore astrocytes morphological changes; astrocyte-specific RNA sequencing (RNA-Seq) analysis were performed to capture transcriptome-wide alterations; ATP and OCR levels of primary astrocytes were measured followed by YL-0919 incubation. In summary, we found that YL-0919 alleviated CRS-induced depressive-like behaviors faster than fluoxetine and attenuated number and morphologic deficits in astrocytes of depression mice; YL-0919 improved astrocyte energy metabolism and mitochondrial oxidative phosphorylation in astrocytes. Our study provided evidence that YL-0919 exerted a faster-onset antidepressant effect on CRS-mice possibly via astrocyte structural remodeling and mitochondria functional restoration.